2008
DOI: 10.1148/rg.282075030
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Idiopathic Spinal Cord Herniation

Abstract: Idiopathic spinal cord herniation, unlike spinal cord herniation with a known traumatic or postoperative origin, is a relatively rare condition; however, it has been diagnosed and reported with increasing frequency in recent years. Such herniation most often occurs in the thoracic spine, between the T4 and T7 vertebrae. Brown-Séquard syndrome is the most frequently reported clinical feature. Early manifestations may include numbness and decreased temperature sensation in the legs, gait disturbances, pain, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 16 publications
3
79
0
4
Order By: Relevance
“…Several cases presented with less typical constellations of symptoms, including bilateral lower limb motor weakness, myoclonic episodes and focal position-related radicular pain. This correlates with previously documented clinical manifestations of similar cohorts [7].…”
Section: Case Reviewsupporting
confidence: 91%
See 1 more Smart Citation
“…Several cases presented with less typical constellations of symptoms, including bilateral lower limb motor weakness, myoclonic episodes and focal position-related radicular pain. This correlates with previously documented clinical manifestations of similar cohorts [7].…”
Section: Case Reviewsupporting
confidence: 91%
“…In a relevant recent review on imaging of this condition [7], MRI was considered sufficient for the diagnosis of cord herniation in most cases, with myelography and CT assessment for clarification in equivocal cases. In our local experience we have found that the routine use of three-dimensional volume T 2 * sequences (such as CISS) in these cases provide high-resolution images which aid the surgical decision-making process while limiting the need for an invasive procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, idiopathic spinal cord herniation was found on CT SAG T2WIs in two patients. Idiopathic spinal cord herniation is also known as spontaneous transdural spinal cord herniation and is a rare cause of thoracic myelopathy (10)(11)(12). However, it has been reported with increasing frequency in recent years (10).…”
Section: Treatment For Pathologic Lesions On Additional Ct Sag T2wismentioning
confidence: 99%
“…Clinical findings are nonspecific, and patients are typically affected by a slowly progressive, Brown-Séquard syndrome or paraparesis. 2 A variety of theories have been postulated to explain the pathogenesis of this entity, but the exact cause of dural defects remains unclear. 1 Surgical treatment to restore a herniated cord to its normal intradural position is mandatory for maximum reversal of neurologic deficits.…”
mentioning
confidence: 99%
“…These increases may be due to a growing awareness among clinicians and radiologists and to improvements in MR imaging quality. [2][3][4] A well-defined set of MR imaging diagnostic criteria has been established for STSCH 2,[4][5][6] ; however, little has been said about postoperative MR imaging of changes in the spinal cord and adjacent structures. Less than half of the cases reported in the literature have described postoperative MR imaging features after reduction of spinal cord herniation 1,4,[7][8][9][10] ; none provided descriptions of a rational analysis; and in cases of complications, few have performed time-related assessments of the findings.…”
mentioning
confidence: 99%